The different subtalar ligaments show significant differences in their mechanical properties. Issue 7 (October 2022) - Michels, Frederick; Taylan, Orçun; Stockmans, Filip; Vereecke, Evie; Scheys, Lennart; Matricali, Giovanni
Highlights: The ACaL-ITCL is a rather stiff ligament with a relative high failure load. This supports the function of apposition of the calcaneus to the talus. The CL is a compliant ligament with a low failure load. The low failure load makes this ligament more vulnerable to injury. A gracilis tendon graft seems more appropriate to reconstruct a CL or CFL than a stiffer synthetic ligament. A partial rupture of the subtalar ligaments was the most common injury pattern after uniaxial loading to failure. Further research about injury patterns is needed as the surgical technique should be adapted accordingly. Abstract: Background: Today, the relative contribution of each ligamentous structure in the stability of the subtalar joint is still unclear. The purpose of this study is to assess the material properties of the different ligamentous structures of the subtalar joint. Methods: Eighteen paired fresh-frozen cadaveric feet were used to obtain bone–ligament–bone complexes of the calcaneofibular ligament (CFL), the cervical ligament (CL) and the anterior capsular ligament-interosseous talocalcaneal ligament complex (ACaL-ITCL). The samples were subjected to uniaxial testing to calculate their respective stiffness and failure load. Results: The stiffness of ACaL-ITCL complex (mean: 150 ± 51 N/mm, 95% confidence interval (CI): 125.0–176.6 N/mm) was significantly higher than both CFL (mean: 55.8 ± 23.0 N/mm, CI: 43.8–67.7 N/mm) and CL (mean: 63.9 ± 38.0 N/mm, CI: 44.4–83.3 N/mm). The failure load of both the ACaL-ITCL complex (mean:382.5 ± 158 N, CI: 304.1–460.8 N) and the CFL (mean:320.4 ± 122.0 N, CI: 257.5–383.2 N) were significantly higher than that of the CL (mean:163.5 ± 58.0 N, CI: 131.3–195.7 N). The injury pattern demonstrated a partial rupture in all CFL and ACaL-ITCL specimens and in 60% of the CL specimens. Conclusion: The CFL, CL and ACaL-ITCL show significant differences in their intrinsic mechanical properties. Both the CFL and CL are more compliant ligaments and seem to be involved in the development of subtalar instability. Based on the material properties, a gracilis tendon graft seems more appropriate than a synthetic ligament to reconstruct a CL or CFL. A partial rupture was the most commonly seen injury pattern in all ligaments. A fibular avulsion of the CFL was only rarely seen. The injury patterns need further investigation as they are important to optimize diagnosis and treatment.